Teacher Obstacles in Preparing Learning Implementation Plans at Madrasah Miftahussudur Banten - Pradika, Ayu Ratih Rizki (KOLABORASI: Journal of Multidisciplinary, 2024)
The teacher is a component that is very influential on the creation of quality educational processes and outcomes. Qualified teachers will make plans for the learning process. Developing a Learning Implementation Plan that will be used during the learning process is one aspect of learning planning. The number of duties and responsibilities of teachers in activities in class and also at school, so that teachers feel that there is a limited time in preparing the lesson plan to be less than optimal. This study aims to determine the obstacles of Banten Miftahussudur teachers in compiling a Learning Implementation Plan both in terms of problems, constraints and efforts made by the Banten Miftahussudur teachers in overcoming obstacles in the preparation of a Learning Implementation Plan. In its implementation, this study uses a qualitative research approach with descriptive analysis method. This study found that the teachers at Madrasah Miftahussudur Banten already understood the lesson plan quite well. In general, teachers at Madrasah Miftahussudur Banten have understood the nature and purpose of preparing a Learning Implementation Plan. In overcoming various problems and obstacles as well as obstacles faced by teachers in the preparation of the Learning Implementation Plan for Madrasah Miftahussudur Banten Teachers, several efforts were made.